The Influence of Outflow Feedback in Clumps - Qiang Li; Mingyue Li; Li Zhang; SongPeng Pei; Zhengxue Chang; Yi Zhang (The Astrophysical Journal, 2023)
We analyzed the influence of outflow feedback from two perspectives: turbulent support and potential disruptive effect, of which 694 clumps and 188 have been identified as outflow candidates. For turbulent support, we find the slopes of E _turb − R _clump (turbulent energy and radius of the clump) and P _turb − R _clump (turbulent momentum and radius of the clump) have no difference and are consistent with expected values whether there is outflow feedback in clumps or not. The ratios of the outflow energy and momentum to the turbulence energy and momentum ( E _flow / E _turb , P _flow / P _turb ) show that the majority of clumps have not enough energy and momentum to support turbulence. Meanwhile, there is no correlation between the velocity dispersion and radius. For potential disruptive effects, we conclude that it is impossible for the outflow activities to disrupt entire clumps and as the mass of the clumps increases, the clumps becomes harder to destroy. Finally, we do not see evidence that the virial parameter changes significantly whether the clumps have outflow candidates or not.